Crystal structure of S-methyl ß-N-(methylacetyl)methylenedithiocarbazate, C6H10N2OS2 - Tarafder, Μ.Τ.H.; Saravanan, N.; Crouse, K.A.; Yamin, Β.M.; Fun, H.-K.; Raj, S.S.S.; Razak, I.A. (Walter de Gruyter GmbH, 2001)
C 6HION2OS2, monoclinic, P\2\tn\ (No. 14), a = 4.2699(1) Ä, b= 13.7544(2) Ä, c = 15.8280(4) Ä, β = 97.263(1)°, V = 922.1 Ä3 , Ζ = 4, R(F) = 0.063, wR^F2 ) = 0.173, Γ =29 3 Κ